»Avec mon arme, la musique« Politisches Engagement exilierter Musikerinnen und Musiker im Kontext des Front Populaire - Amann-Rauter, Milena (Edition Text + Kritik, 2023)
Bread, peace, freedom - this was the motto of the French Popular Front (Front Populaire), which formed France's government from 1936 to 1938. With its anti-fascist focus, the French Popular Front movement was also attractive to refugees from Nazi Germany and offered them a platform to make a political statement. Exiled musicians helped to shape the Popular Front by making music, composing and agitating for the common cause. The book sheds light on the multifaceted involvement of exiled musicians in the Front Populaire. This includes their membership in agitprop and cabaret groups, their participation in political films and radio broadcasts, their composing and performing of political pieces of music, their reflection on political circumstances in the context of the Saar referendum campaign or the Workers' Music Olympics in Strasbourg. Paul Arma (1904-1987), Paul Dessau (1894-1979), Hanns Eisler (1898-1962), Joseph Kosma (1905-1969), Franz Landé (1893-1942), Marianne Oswald (1901-1985), Louis Saguer (1907-1991), Eberhard Schmidt (1907-1996) and Cora Schmidt-Eppstein (1900-1939) are the central protagonists of the study.